(untitled) (ELang | An English Language Education Journal, 2023)
This research paper entitled "Enhancing Students’ Reading Comprehension by Using RCRR (Read, Cover, Remember and Retell)". This study is a Pre-experiment research conducted on seventh grade students of SMP KP Baros. This study aims to determine whether the RCRR (Read, Cover, Remember and Retell) technique is effective or not to improve students’ reading comprehension of descriptive text at SMP KP Baros. The sample of this study was 38 students of class VII C. The instruments used were pre test, post test and questionaire. The pre test was given to determine students’ reading ability before being given treatment and the post test was given to students to measure whether there was progress in reading comprehension. The results showed that the use of the RCRR technique (Read, Cover, Remember and Retell) showed positive results. This is evidenced by the calculation of the t-test, the results of the calculation, with df = N-1 = 38-1 =37, at p = .05 with two sides (two tailed), the critical value of t is 2.026, because the obtained t of 13.2 is greater or higher than the critical value of t table of 2.026 (13.2 > 2.026). Therefore (Ha) is accepted and (Ho) is rejected. This means, the use of RCRR (Read, Cover, Remember and Retell) technique is effective to improve students’ reading comprehension in the first grade of SMP KP Baros. Then, from the result of questonaire students showed a positive response to the use of the RCRR (Read, Covet, Remember and Retell) technique. It means students enjoyed their learning using RCRR (Read, Cover, Remember and Retell) and it made them understand the context easily.